From Floods to Trauma: Examining the Link Between Individual Traits and PTSD in Kalibaru, Banyuwangi - Maulina, Yeni (Al-Hijrah Indonesia, 2025)
The flood disaster has an impact on the community, namely damaged buildings, loss of life, and psychological impacts such as fear, anxiety, sadness, and despair. The purpose of this study was to determine the relationship between individual characteristics and Post Traumatic Stress Disorder (PTSD) in victims of flash floods in Krajan and Tegal Pakis Hamlets, Kalibaru District, Banyuwangi. This study was conducted using a cross-sectional research design with respondents, namely victims of flash floods in Krajan and Tegal Pakis Hamlets, Kalibaru District, Banyuwangi, with a sample of 181 using a purposive sampling technique. This study showed that most respondents were in the adult age category, with a percentage of 47.5% of the total respondents. Most respondents were female, with a percentage of 62.4%; most had a high school education, and most were homemakers. The most marital status was married, and most respondents experienced trauma due to losses experienced due to the disaster. Based on the analysis conducted using Spearman, a relationship was found between individual characteristics and the level of PTSD in respondents on the variables of age and gender. However, other variables such as education, occupation, marital status, and injuries experienced did not have a significant relationship with PTSD in respondents.